2022
DOI: 10.1186/s12887-022-03399-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of parental weight change on the incidence of overweight and obesity in offspring

Abstract: Background There is limited information on the association of parental weight change with overweight and obesity in offspring. This study aimed to investigate the association between parental weight change and incident overweight and obesity in offspring. Methods This longitudinal cohort study included 2,963 parent–offspring trios who participated in at least two waves of the China Health and Nutrition Survey. The children without overweight and ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Obesity is a complex disease influenced by genetics and environment, where parents play an important role in both aspects. In our study, children and adolescents with overweight parents were found to be nearly twice as likely to develop MHO and MUO as those with non-overweight parents, and the conclusion was similar to previous evidence including cross-sectional and longitudinal studies (43,44). On the one hand, parental obesity could predict similar obesity susceptibility in their children due to genetic background (45).…”
Section: Discussionsupporting
confidence: 91%
“…Obesity is a complex disease influenced by genetics and environment, where parents play an important role in both aspects. In our study, children and adolescents with overweight parents were found to be nearly twice as likely to develop MHO and MUO as those with non-overweight parents, and the conclusion was similar to previous evidence including cross-sectional and longitudinal studies (43,44). On the one hand, parental obesity could predict similar obesity susceptibility in their children due to genetic background (45).…”
Section: Discussionsupporting
confidence: 91%
“…Due to evident timing and ethical issues, human studies investigating these aspects are limited and varied; thus, this systematic review was carried out in order to summarize the state-of-the-art findings. The majority of included studies [22][23][24][27][28][29][30][31] considered BMI as paternal parameter on varying offspring outcomes. Four studies studied cord blood DNA methylation, all of which showed the impact of higher paternal BMI on DNA methylation of different genes.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies assessed paternal BMI and birthweight showing that after adjustment for maternal age, smoking status, BMI of the other parent, the newborn's birth weight and gender, the infant birthweight increased by 42.2 g (95% CI 29.5-54.8; P < 0.0001) per unit increase in maternal pregravid BMI and 10.7 g (95% CI 0.5-20.9; P = 0.04) per unit increase in paternal pre-gravid BMI [29] and that a paternal BMI > 25 was associated with increased offspring birth weight compared with paternal BMI less than 25 (mean [SD] z score, 0.38 [0.91] vs 0.11 [0.96]; P = .004) [27]. Another study showed that paternal persistent overweight and obesity were also associated with higher risk of overweight and obesity in offspring at follow-up [23]. Interestingly, one study reported a significantly smaller infant triceps, suprailiac, and thigh skinfold thickness measurement, as well as percent fat mass, in offspring of fathers with a BMI >35 compared with that observed in offspring of lean fathers [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Furthermore, parental obesity increases the risk of childhood obesity. 11 Eventually, by 2050, 60% of males and 50% of females will be obese. 12 This leads to an exponential increase in the worldwide incidence of NAFLD.…”
Section: Introductionmentioning
confidence: 99%